Banks versus Venture Capital: Project Evaluation, Screening, and Expropriation - Ueda, Masako (Journal of Finance, 2004)
ABSTRACT Why do some start‐up firms raise funds from banks and others from venture capitalists? To address this question, I study a model in which the venture capitalist can evaluate the entrepreneur's project more accurately than the bank but can also threaten to steal it from the entrepreneur. Consistent with evidence regarding venture capital finance, the model implies that the characteristics of a firm financing through venture capitalists are relatively little collateral, high growth, high risk, and high profitability. The model also suggests that tighter protection of intellectual property rights encourages entrepreneurs to finance through venture capitalists.